World-class football players' visual exploratory behaviour: a close-up video analysis in UEFA Champions League matches - Pedersen, D. N. (2016)
The overall purpose of this study was to examine how football players explore the environment and use the information to prospectively control subsequent actions with the ball. A real world field study was conducted and Gibson`s (1966; 1979) ecological approach to visual perception was used as conceptual framework. The relationship between visual exploratory behaviour (VEB) and performance, VEB and various situational characteristics, and the timing of the players` VEB were examined. Eight world-class midfield and forward players (M = 31.5 years, SD = 3.25) were filmed "close-up" in five matches of the 2014/2015 UEFA Champions League group stages (M = 56.13 minutes, SD = 40.36). These footages were edited together with the official UEFA match broadcast, creating a split screen video for further examination of a total of 269 situations and 851 visual exploratory behaviours (searches). Results suggests a positive relationship between VEB prior to receiving the ball and performance, where players are more successful in their forward actions and complete more penetrating forward passes when exploring more compared to when exploring less. Further, when players perform extensive VEB, they execute more actions in the attacking direction, are more forward oriented when receiving, and are under less defensive pressure compared to when exploring less. Finally, the players` timing of each search suggests that they initiate significantly more searches than expected in the immediate moment the ball position and/or direction is determined. In conclusion, this study suggests a positive relationship between VEB and performance in football, and that VEB is used by players to get in a better position to execute their subsequent actions. In addition, a VEB timing pattern is proposed. The development of visual exploratory behaviour should be highly emphasised in football players` daily training, and some practical implications are presented.